Pengetahuan Lokal Masyarakat Dataran Rendah Cianjur Selatan Dalam Pemanfaatan Sumber Daya Air - Silmi Syahidah (Universitas Insan Cendekia Mandiri, 2020)
Water is a basic necessity for people's daily lives. Each region has a local knowledge about water resources that keeps their needs met. This research explains how people in hilly lowland areas with the rivers under agricultural land can survive with their traditional knowledge. The study was conducted in Karangwangi Village, South Cianjur. Research studies have focused on different types of water sources and and utilization by the local people. The research method used was mixed-method with observational data collection techniques, semi-structured interviews and structured interviews. Based on information from the community, the water source in Karangwangi Village is not only a wahangan but also hulu cai, sirah cai, cai nyusu, wells, solokan, situ, balong and cai hujan. All of these water sources in ancient times can be used for all needs such as ibak, nyeuseuh, nginum, cooking, agriculture, fisheries. How to use it is done traditionally by using bamboo, timba, bucket. Quality and quantity of river water changes every season and the use of pesticides makes people sort water sources depend on their needs.Keywords :traditional knowledge, management water resource, water etnoecology